O03 Flow diversion for internal carotid artery aneurysms with compressive neuro-ophthalmologic symptoms: results from an international multicenter study. (29th August 2022) - Gawlitza, M; Kaiser, D; Soize, S; Lobsien, D; Maus, V; Fischer, S; Klisch, J; Styczen, H; Janot, K; Deuschl, C; Abdullayev, N; Kabbasch, C; et al.
Abstract : Introduction: Data on the safety and efficacy of flow diverters (FD) for the treatment of unruptured internal carotid artery (ICA) aneurysms with compressive neuro-ophthalmological symptoms are scarce. Aim of the Study: To provide evidence compiling the largest dataset published to date. Methods: Data from nine neurointerventional departments, encompassing all patients treated since 2015 with a FD for unruptured aneurysms of the ICA with signs of compressive cranial nerve symptoms (CN II, III, IV, VI), were pooled. Results: 55 patients with 55 aneurysms were treated. After 13±10.4 months, 37.3% of patients recovered completely and 35.3% at least partially from their neuro-ophthalmological symptoms. In multivariable models, a longer delay between symptom onset and treatment was associated with higher odds for incomplete recovery and lower odds for any improvement (aOR 1.03 [1.01 – 1.7], p=0.047 and 0.04 [0 – 0.81], p=0.020). Treatment-related morbidity and mortality rates were 7.4% and 3.7%. Increasing age (OR per decade 3.2 [95% CI 1.23–8.49]; p=0.02) and dual antiplatelet therapy with Ticagrelor (OR 13.9 [95% CI 1.16–165.97]; p=0.04) were significant risk factors. After 13.3 ± 10.5 months, rates of complete aneurysm occlusion, neck remnant and aneurysm remnant were 74%, 14% and 12%. Incomplete occlusion at follow-up was less frequently observed in aneurysms treated with additional coil embolization (OR 0.1 [95% CI 0.01–0.86]; p=0.04). Conclusion: FDS are effective to treat patients with compressive aneurysms of the ICA causing neuro-ophthalmological symptoms, especially when treatment is initiated early after symptom onset, but serious complications are not rare. References: Boulouis G, Soize S, Maus V, et al . Compressive Aneurysm Study Group. Flow Diversion for Internal Carotid Artery Aneurysms with Compressive Neuro-Ophthalmologic Symptoms: Clinical and Anatomical Results in an International Multicenter Study. J Neurointerv Surg . 2021 Nov 18:Neurintsurg-2021-018188. DOI: 10.1136/Neurintsurg-2021-018188. EPUB AHEAD of Print. PMID: 34795018. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Consultancy contract with Phenox, proctoring contract with MicroVention, member of the clinical event committee for a study on a flow diverter, sponsored by Microvention. Received stents from Phenox for research purposes.